Pengangkutan di bandar: isu dan penyelesaian - Shafii, Haryati; Musa, Sharifah Meryam Shareh (UTHM Publisher, 2010)
Generally, quality of life of urban population is heavily dependent on social facilities provided within the environment. One of the most important facilities is transportations. Study on transportation mode in an urban area is especially very important because for almost every individual living in a large and densely populated area, mobility is one of the most crucial issues in everyday life. Enhance mobility, faster journey to work and less pollution from petrol-propelled vehicles can increase the quality of life, which in turn lead to a sustainable urban living. The study present transportation mode usage issues faced by community related to quality of life in an urban area. This study identifies several issues of transportation mode in urban areas and its impact on the quality of life. The study areas are Putrajaya, Kuala Lumpur and Bandar Kajang, Selangor. The methodology used in this research is secondary and primary data. The questionnaires for the survey were distributed from May 2008 to Jun 2008. These researches were conducted on 144 respondents for to evaluate their perception of transportation mode correlated to the quality of life. The collected data were then analyzed using “Statistical Packages for the Social Science” (SPSS). The respondents comprise of 61 males and 84 females from the age group of 18 to 57 years. This study identifies the percentage of public transportation mode usage in urban area, such as buses (16.7%), train (ERL, monorail and commuter-6.4%); which is very low compared to owning personal car (45.8%) and motorcycle (25.4%).The result shows owning personal car is the highest (45.8%) in three study areas and monorail and taxi are the lowest (1.4%). The Chi Square Test shows that among the mode transportation with traffic jam is quite difference in Kuala Lumpur, Putrajaya and Kajang. Analysis of the Chi Square Test shows the result is 0.000 (two sides) to respondent answering “yes” and analysis of Spearman Correlation test is P =0.362 and significant to level = 0.000. This study also identifies the impact of mode of transportation to community. However impact due to traffic jam is very critical (88.8%) in three areas which between > 10-15 minutes and >40-45 minutes This research also indicated some psychologies effect. The psychological effects of people with the mode of transportation in urban areas are tiredness, headache and stress. The study concludes with some suggestion on future transportation development towards higher consideration for community in urban areas which can contribute to a higher quality of life.